BLOCKCHAIN-ENABLED ALGORITHMIC GOVERNANCE AND FRONTIER PERFORMANCE IN COOPERATIVE AGRIBUSINESS: INTEGRATING PRODUCTIVITY, TECHNOLOGY-GAP, AND TRANSACTION-COST ANALYSIS - Riswandi, Dadang Iwan; Saleh, Rahmat (LPPM Universitas Jambi, 2026)
Blockchain technology is increasingly adopted in agribusiness supply chains to improve transparency, traceability, and coordination. However, previous studies have largely examined productivity, technology adoption, and transaction costs separately, providing limited understanding of how blockchain simultaneously affects production and governance performance. This study investigates the effects of blockchain adoption on technical efficiency, productivity growth, technology-gap reduction, and transaction-cost performance in a vertically integrated cassava–tapioca cooperative agribusiness system in Indonesia. A balanced panel dataset of 30 cooperative decision-making units (DMUs) observed from 2019–2025 was analyzed using an integrated framework combining Dynamic Network Data Envelopment Analysis (DEA), Stochastic Frontier Analysis (SFA), the Malmquist Productivity Index (MPI), Meta-Frontier Analysis, and a Transaction-Cost Frontier Model. Blockchain adoption substantially improved organizational performance. Mean DEA technical efficiency increased from 0.742 to 0.861 (+15.98%), while SFA efficiency increased from 0.756 to 0.872 (+15.34%). Productivity growth accelerated after adoption, with MPI values ranging from 1.062 to 1.097, primarily driven by technological change. The Technology Gap Ratio increased from 0.841 to 0.921, indicating closer convergence toward the meta-frontier. Transaction-cost inefficiency declined by 35.5% among blockchain adopters, reflecting significant reductions in monitoring, verification, and coordination costs. The novelty of this study lies in conceptualizing blockchain as an algorithmic governance mechanism and integrating productivity, technology-gap, and transaction-cost frontier analyses within a single framework. The findings show that blockchain functions not only as a digital technology but also as a governance innovation capable of simultaneously shifting production and coordination frontiers, offering practical guidance for digital transformation in cooperative agribusiness systems.